Ökonomische Auswirkung der COVID-19-Pandemie in der Allgemein- und Viszeralchirurgie: Ein Vergleich von Leistungs- und Erlösdaten zweier Kliniken aus Krankenhäusern unterschiedlicher Versorgungsstufen - Binder, Johannes; Brunner, Maximilian; Maak, Matthias; Denz, Axel; Grützmann, Robert; Krautz, Christian; Weber, Georg (Chirurg, 2021)
Background: During the first wave of the coronavirus disease 2019 (COVID-19) pandemic, German hospitals were required to limit the capacity for elective surgery to prevent the healthcare system from general overload. In March 2020, the German government passed the COVID-19 Hospital Relief Act that guaranteed compensation payments for these limitations. In this study the regional impact of this intervention were analyzed. Material and methods: The performance data and revenue figures for the departments of general and visceral surgery of the University Hospital of Erlangen (UKER) and the District Hospital St. Anna Höchstadt/Aisch (KKH) during the period from 1 April to 30 June 2019 were compared with the respective period in 2020. Results: There was a significant decrease in bed occupancy rates and case numbers of inpatient treatment. The latter declined by 20.06% in the UKER and 60.76% in the KKH. Nononcological elective surgery was reduced by 33.04% in the UKER and 60.87% in the KKH. The number of emergency procedures remained unchanged in the UKER, while they decreased by 51.58% in the KKH. The revenues from diagnosis-related groups (DRG) decreased by 22.12% (UKER) and 54% (KKH), respectively. After taking compensation payments and savings from variable material costs into account, the UKER recorded a loss of −3.87%, while there was a positive revenue effect of 6.5% in the KKH. Discussion: The nonselective restriction of elective surgery had a significant impact on patient care and revenue figures at both locations. With respect to the increase of intensive care capacities, such untargeted measures do not appear to be efficient. In addition, the fixed rate of compensation payments led to an unbalanced distribution of the financial aid between the two departments.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Coronavirus; DRG billing data; Hospital Relief Act; Surgery; Treatment quality